2003
DOI: 10.2337/diabetes.52.5.1204
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Iron-Available, Polyphenol-Enriched, Carbohydrate-Restricted Diet to Slow Progression of Diabetic Nephropathy

Abstract: Diabetic nephropathy has become the leading cause of uremia. Several lines of evidence suggest dietary factors other than protein intake have a substantial role in the progression of diabetic nephropathy to end-stage renal disease. The present investigation was initiated to evaluate whether a carbohydrate-restricted, low-ironavailable, polyphenol-enriched (CR-LIPE) diet may delay and improve the outcome of diabetic nephropathy to a greater extent than standard protein restriction. To this aim, 191 diabetic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 46 publications
3
49
0
1
Order By: Relevance
“…Studies were conducted in some or all of the United States, Canada, Europe, Asia, and Oceania, with trial results published between 1992 and 2013. A variety of interventions were assessed, including BP lowering (16 trials 12,13,17,19,[21][22][23][24][25][26]28,29,[31][32][33][34] ), lipid-lowering therapy (3 trials 9,11,15 ), intensive glucose-lowering therapy (4 trials 16,20,27,30 ), anemia therapy (2 trials 14,18 ), dietary intervention (1 trial 10 ), and chelation therapy (1 trial 8 ).…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were conducted in some or all of the United States, Canada, Europe, Asia, and Oceania, with trial results published between 1992 and 2013. A variety of interventions were assessed, including BP lowering (16 trials 12,13,17,19,[21][22][23][24][25][26]28,29,[31][32][33][34] ), lipid-lowering therapy (3 trials 9,11,15 ), intensive glucose-lowering therapy (4 trials 16,20,27,30 ), anemia therapy (2 trials 14,18 ), dietary intervention (1 trial 10 ), and chelation therapy (1 trial 8 ).…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…The trials had a sample size that ranged from 50 to 17,118 participants with follow-up periods from 1.6 to 10.0 years. Of the 27 trials identified, 3 were single-center studies [8][9][10] and 24 were multicenter studies. Studies were conducted in some or all of the United States, Canada, Europe, Asia, and Oceania, with trial results published between 1992 and 2013.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, the pathogenic role of iron in progression is indicated by the observation that progression can be prevented either by an iron-deficient diet or chelators (76 -78). More specifically, in diabetes, a recent randomized trial involving 191 patients with diabetes, proteinuria, and a decreased glomerular filtration rate showed that a low-iron-available, carbohydraterestricted, polyphenol-enriched diet compared with a standard proteinrestricted diet had a renoprotective effect (67).…”
Section: The Role Of Iron In Complications Of Diabetesmentioning
confidence: 99%
“…21 The small but growing literature on the effects of induced iron depletion/deficiency in various experimental models of oxidative or inflammatory injury strongly supports beneficial effects of eliminating storage iron. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Correlation of in vitro with in vivo endothelial iron status will be assisted by future studies into the basis for an interesting phenomenon seen in human umbilical vein endothelial cells (HUVEC). Sensitivity of HUVEC to oxidative injury or high glucose levels decreases sharply with subculture in vitro after a few passages.…”
Section: See Page 1577 Endothelial Iron Status In Vivomentioning
confidence: 99%